Conflict of Interest in Legal Consultancy Practice: A Review of Legal Professional Ethics - Manuel Mekel (West Science Law and Human Rights, 2026)
This article provides a comprehensive analysis history: of conflict of interest in legal consultancy practice from the perspective of Indonesian legal professional ethics. The research employs a normative legal methodology with statute, conceptual, and case approaches. The study examines the definition, forms, and manifestations of conflict of interest in legal practice, analyzes the prohibitions established under the Advocate Code of Ethics and Law Number 18 of 2003, and evaluates the legal and ethical consequences of such conflicts. The findings reveal that conflict of interest represents a systemic threat to the integrity of the legal profession, undermining client trust, compromising professional independence, and distorting the administration of justice. The article identifies significant regulatory gaps in the current ethical framework and proposes structural reforms including the mandatory implementation of conflict screening systems, the adoption of Chinese Wall protocols, and the strengthening of Honor Council enforcement mechanisms to prevent and address conflicts of interest in legal consultancy practice.